Perception of the Wogo Village Community Regarding the Waja Betho Tradition in Bamboo Forest Conservation: Persepsi Masyarakat Desa Wogo Mengenai Tradisi Waja Betho Dalam Pelestarian Hutan Bambu - Maria Dewiyulianti Pida Kadju; Sumarmi; Tuti Mutia (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Bamboo is a versatile plant that offers a diversity of ecosystem services for the environment, so its existence needs to be preserved. The existence of bamboo in rural areas, especially in Wogo Village, is closely related to the culture and traditions of the local community, which can be used to regulate the lifestyle of the community towards the existence and preservation of bamboo forests. Community perception will help see the perspective, response and sensing of a group of people in an area towards events or phenomena that occur in their environment. This research examines community perceptions of the Waja Betho Tradition, as one of the community's local knowledge in relation to the preservation of bamboo forests. To explore information about the data, a descriptive qualitative method is used and the search for accurate information data in the field through observation, interview and documentation techniques to be able to study more deeply. Based on the results obtained, it can be concluded that some village communities already have the perception that the waja betho tradition which is an ancestral heritage plays an important role in the preservation of bamboo forests. The community's perception of the waja betho tradition in preserving bamboo forests is influenced by individual interests, interaction with the environment and economic motives. The waja betho tradition also contains environmental conservation values in this case to preserve bamboo, where there is a prohibition on harvesting bamboo for a specified period of time to keep the bamboo able to grow lush and quality, before it can finally be used again.